Color-Coding Print Versus Digital Technology to Teach Functional Community Knowledge to Rural Students With Autism and Complex Communication Needs. (December 2021) - Robertson, Colleen E.; Spooner, Fred; Wood, Charles L.; Pennington, Robert C.
Post-school outcomes in the areas of health, safety, and independent living are poor among students with complex communication needs and autism spectrum disorder, particularly for those in rural areas. This study examined the comparative effects of print versus digital technology instruction on participants' cumulative accuracy of answering Wh (who, what, where, and when) functional community knowledge comprehension questions during print and digital technology instructional sessions, with four high school–age students with moderate to severe intellectual disabilities and autism. Using a single-case research, alternating treatments design, the researchers provided instruction to the participants through a model-lead-test procedure with shared reading, color-coded vocabulary words, and adapted stories following a Fitzgerald Key Format, using print and digital technology instructional conditions. All participants made gains across conditions. Contributions to the research literature, limitations of the study, recommendations for future research, and implications for practice are discussed.